2021
DOI: 10.1021/acs.jmedchem.0c01914
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Reactive Oxygen Species Production

Abstract: Reactive oxygen species (ROS) are involved in physiological cellular processes including differentiation, proliferation, and apoptosis by acting as signaling molecules or regulators of transcription factors. The maintenance of appropriate cellular ROS levels is termed redox homeostasis, a balance between their production and neutralization. High concentrations of ROS may contribute to severe pathological events including cancer, neurodegenerative, and cardiovascular diseases. In recent years, approaches to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 217 publications
1
18
0
Order By: Relevance
“…Similar to a previous report ( Li et al, 2021 ), we found that lycorine treatment stimulated high levels of ROS production in HSFs and produced high levels of ROS appeared to be responsible for the pro-apoptotic and anti-fibrotic activities of lycorine. Supportively, treatment with NAC, a ROS scavenger ( Sassetti et al, 2021 ), alone did not affect the apoptosis of HSFs, but significantly mitigated or abrogated the pro-apoptotic and anti-fibrotic effects of lycorine in HSFs by increasing the MMP, reducing cytoplasm cyt-C translocation and apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to a previous report ( Li et al, 2021 ), we found that lycorine treatment stimulated high levels of ROS production in HSFs and produced high levels of ROS appeared to be responsible for the pro-apoptotic and anti-fibrotic activities of lycorine. Supportively, treatment with NAC, a ROS scavenger ( Sassetti et al, 2021 ), alone did not affect the apoptosis of HSFs, but significantly mitigated or abrogated the pro-apoptotic and anti-fibrotic effects of lycorine in HSFs by increasing the MMP, reducing cytoplasm cyt-C translocation and apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…The same trend was observed for positive control which further confirms the potency of the purine derivatives towards the removal of excess iron from cells via its chelation. It is known that the generation of ROS is directly dependent on the iron concentration and Fe 2+ induces such intracellular processes [15b,28] . We checked the effect of added purine derivatives on ROS concentration inside the cells by measuring the DCF fluorescence intensity [29] .…”
Section: Resultsmentioning
confidence: 99%
“…Requirement 2: ROS and radicals. As reviewed recently by Sassetti et al [ 20 ], the main source of intracellular ROS are mitochondria, i.e., incomplete reduction within the mitochondrial respiratory chain (superoxide). Furthermore, enzymes in the endoplasmatic reticulum, peroxisomes and the plasma membrane (such as NOX, NADPH oxidases) as well as non-enzymatically via the Fenton reaction represent sources of ROS [ 9 , 20 ] that might represent the starting point of ferroptosis induction—provided that the other mentioned requirements are fulfilled.…”
Section: Introductionmentioning
confidence: 99%